Archetypes and collective unconscious in the plastic arts to leave of the psychology of C.J.Jung. - León del Río, Mª Belén (Arte, Individuo y Sociedad, 2009)
The man's old history you rediscovering nowadays in the symbolic images and myths that for the humanity being the art an important canalizador to understand the modern individual's deeper essence. symbols made it the school of analytic psychology of C. G. Jung, for this author the human mind has its own history and the psyche conserves many rakes of the previous stages of its development. It is scorn those contents, but unconsciously we respond to them and the symbolic forms with which they are expressed. In the world of the art these archetypal images are very abundant belonging together to a that conserves and it transmits the humanity's psychological common inheritance. Those symbols are so old and unknown that our objective is to discover them to understand the plastic work well, acquiring a better knowledge of their origins and meaning. The lines of investigation of this article will have a pouring double: on one hand it will be studied the creative processes in the artistic manifestations, valuing them inside their cultural context and of their to become temporary and on the other hand it will be centered in the investigation and the study in the sculptural, pictorial and architectural ways with analysis of their symbols with the objective of developing the why of these processes and their archetypal meaning in the art.
Keywords: Symbol; Plastic arts; Imagination; Archetype; Circle; Inspiration; Unconscious; Send it; Myth; I impel lúdico; Cuaternidad; Intuition; Fantasy; Yes-same; Process of individuation